Medication Review and Patient Outcomes in an Orthopedic Department: A Randomized Controlled Study. Issue 2 (June 2018) - Lisby, Marianne; Bonnerup, Dorthe Krogsgaard; Brock, Birgitte; Gregersen, Pernille Axelsen; Jensen, Joern; Larsen, Maren-Lis; Rungby, Joergen; Sonne, Jesper; Mainz, Jan; Nielsen, Lars Peter
Abstract : Objective: We investigated the health-related effect of systematic medication review performed by a clinical pharmacist and a clinical pharmacologist on nonelective elderly orthopedic patients. Methods: This is a nonblinded randomized controlled study of 108 patients 65 years or older treated with at least 4 drugs. For the intervention, the clinical pharmacist reviewed the participants' medication after completion of the usual medication routine. Information was collected from medical charts, interviews with participants, and database registrations of drug purchase. Results were conferred with the clinical pharmacologist, and recommendations were delivered directly to the ward physicians. The control was usual medication routine, that is, physicians prescribing admitting orders. The primary outcome was time to the first unplanned contact to a physician after discharge (i.e., general practitioner, emergency department visit, or readmission) during 3-month follow-up. Secondary outcomes included other health-related outcomes, for example, length of in-hospital stay, mortality, and quality of life. Results: Time to the first unplanned contact to a physician was 14.9 days (95% confidence interval, 8.9–21.0) in the intervention group compared with 27.3 days (95% confidence interval, 18.9–35.7) in the controls ( P = 0.05). Overall, no statistically significant differences were seen in the secondary outcomes apart from "number of" and "time to first" emergency department visits, which were in favor of the intervention group. A marked hesitation of the ward physicians to comply with recommendations was noted (18%). Conclusions: The study showed that the patients receiving usual care had a significantly longer time to the first unplanned contact to a physician after discharge; however, the fact that less than 1 of 5 recommendations was adopted by the physicians raises concerns as to whether this finding could be attributable to the intervention.